ANALISIS PENDAPATAN USAHA KOPRA DI DESA LENDE KECAMATAN SIRENJA KABUPATEN DONGGALA - S, Zikriana; Khatima, Husnul (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2023)
Copra, a processed coconut product, has significantly contributed to improving Central Sulawesi province economy. The research location was in Lende village of Sirenja sub district of Donggala district, Central Sulawesi where 31 respondents were selected from a population of 102 copra farmes. The research was conducted from November to December 2020. The results showed that the average copra production produced by the copra farmers in Lende Village was 1,321 kg/production with an average revenue of Rp. 6,048,000/production, while the average production cost incurred by the copra farmers was IDR 1,646,120.97/production leading to an average income of IDR 4,240,175.20/production for the copra farmers.